Pre-Design Empiricism for Information Visualization: Scenarios, Methods, and Challenges - Brehmer, Matthew; Carpendale, Sheelagh; Lee, Bongshin; Tory, Melanie (BELIV '14 Proceedings of the Fifth Workshop on Beyond Time and Errors: Novel Evaluation Methods for Visualization, 2014)
Empirical study can inform visualization design, both directly and indirectly. Pre-design empirical methods can be used to characterize work practices and their associated problems in a specific domain, directly motivating design choices during the subsequent development of a specific application or technique. They can also be used to understand how individuals, existing tools, data, and contextual factors interact, indirectly informing later research in our community. Contexts for empirical study vary and practitioners should carefully consider finding the most appropriate methods for any given situation. This paper discusses some of the challenges associated with conducting pre-design studies by way of four illustrative scenarios, highlighting the methods as well as the challenges unique to the visualization domain. We encourage researchers and practitioners to conduct more pre-design empirical studies and describe in greater detail their use of empirical methods for informing design.